Comparison of group cognitive behavioral therapy and interactive lectures in reducing anxiety during pregnancy: A quasi experimental trial. Issue 43 (October 2016) - Salehi, Fariba; Pourasghar, Mehdi; Khalilian, Alireza; Shahhosseini, Zohreh
Abstract: Background: Anxiety during pregnancy and its adverse effects on mother and baby is a health concern worldwide. This study aimed to investigate the effects of group cognitive behavioral therapy (GCBT) compared with interactive lectures (IL) on anxiety during pregnancy. Methods: This quasi experimental trial was conducted in Sari city, in north Iran, from March to July 2015. Participants were 91 obstetrically and medically low-risk nulliparous women with a mild to moderate anxiety level, as assessed by Spielberger's State-Trait Anxiety Inventory. Participants were selected from the general population by cluster sampling and assigned to 3 groups: a cognitive behavioral therapy (CBT) group (n = 31), an IL group (n = 30), and a control group (n = 30). All participants completed a demographic characteristics form and the Speilberger State-Trait Anxiety Inventory. The inventory was completed again by the CBT and IL groups 4 weeks after the interventions, and 4 weeks after the initial questionnaire by the control group. Data were analyzed with chi-squared tests, independent t -tests, paired t -tests, ANOVA, and Dunnett post hoc test. Results: A significant decline in state and trait anxiety was found in the CBT and IL groups at 4 weeks ( P < 0.001). GCBT was more effective than IL in reducing participants' anxiety, but the difference was not significant ( P > 0.05). Conclusion: GCBT and IL had beneficial effects in reducing anxiety in pregnancy. The psychological status of pregnant women in prenatal care services should be investigated and either of these methods used to manage maternal anxiety, depending on the available healthcare service resources.